Regulation of AMPA receptor trafficking by secreted protein factors - Rennich, Bethany J.; Luth, Eric S.; Moores, Samantha; Juo, Peter (Frontiers in Cellular Neuroscience, 2023)
AMPA receptors (AMPARs) mediate the majority of fast excitatory transmission in the brain. Regulation of AMPAR levels at synapses controls synaptic strength and underlies information storage and processing. Many proteins interact with the intracellular domain of AMPARs to regulate their trafficking and synaptic clustering. However, a growing number of extracellular factors important for glutamatergic synapse development, maturation and function have emerged that can also regulate synaptic AMPAR levels. This mini-review highlights extracellular protein factors that regulate AMPAR trafficking to control synapse development and plasticity. Some of these factors regulate AMPAR clustering and mobility by interacting with the extracellular N-terminal domain of AMPARs whereas others regulate AMPAR trafficking indirectly via their respective signaling receptors. While several of these factors are secreted from neurons, others are released from non-neuronal cells such as glia and muscle. Although it is apparent that secreted factors can act locally on neurons near their sites of release to coordinate individual synapses, it is less clear if they can diffuse over longer ranges to coordinate related synapses within a circuit or region of the brain. Given that there are hundreds of factors that can be secreted from neuronal and non-neuronal cells, it will not be surprising if more extracellular factors that modulate AMPARs and glutamatergic synapses are discovered. Many open questions remain including where and when the factors are expressed, what regulates their secretion from different cell types, what controls their diffusion, stability, and range of action, and how their cognate receptors influence intracellular signaling to control AMPAR trafficking.